Intussusception in an adult with a history of rectal cancer: a case report - Liu, Wei; Li, Feng; Jiao, Cheng; Guo, Jun; Jiao, Yurong; Liu, Guangchao; Zhang, Yao (Frontiers in Medicine, 2025)
This case report details the clinical journey of a 37-year-old male patient who had undergone rectal cancer surgery five years prior to symptom onset. The patient presented with an abdominal mass and intermittent abdominal pain that had been present for approximately two weeks prior to the current hospitalization for treatment. Through a comprehensive array of diagnostic procedures, notably abdominal CT scans and colonoscopies, the presence and precise location of intussusception were ascertained. The surgical management entailed a radical right hemicolectomy supplemented by preventive measures against recurrence. In the postoperative phase, the patient was administered oral medications and subjected to regular follow-up. This case highlights the diagnostic and therapeutic challenges of adult intussusception in postoperative cancer patients and underscores the importance of a multidisciplinary approach. It also emphasizes the need for tailored treatment strategies to optimize patient outcomes.